Direct investigations on strain-induced cold crystallization behavior and structure evolutions in amorphous poly(lactic acid) with SAXS and WAXS measurements. (4th May 2016) - Zhou, Chengbo; Li, Hongfei; Zhang, Wenyang; Li, Jingqing; Huang, Shaoyong; Meng, Yanfeng; Christiansen, Jesper deClaville; Yu, Donghong; Wu, Zhonghua; Jiang, Shichun
Abstract: Strain-induced cold crystallization behavior and structure evolution of amorphous poly(lactic acid) (PLA) stretched within 70–90 °C were investigated via in situ synchrotron small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) measurements as well as differential scanning calorimetry (DSC) measurements. The data obtained from the stretched samples within 70–90 °C showed that all of the formed crystals are disordered α′ form with more compact chain packing than that of the cold crystallization. Upon stretching at 70 °C, the mesocrystal appears first then forms crystal with strain increasing. The stacked structure consisting of less perfect crystalline phase, mesocrystal and oriented amorphous phase emerges at the final stage of stretching. Drawing at 80 °C, only the crystal can be induced at lower strain with higher crystallization rate. With strain increasing, the crystallinity and crystal orientation increase, leading to the formation of analogous 'shish-kebab'. The structure evolution at 90 °C is similar to that at 80 °C, but with much earlier crystallization onset and higher crystallization rate. The difference in strain-induced crystallization behavior of amorphous PLA within 70–90 °C can be attributed to the competition between chain orientation caused by stretching and chain relaxation. It was proposed that the strain-induced mesocrystal/crystal and the lamellae are formed from the mesophase originally existing in PLA glass according to the obtained data. Graphical abstract: Highlights: Strain-induced PLA structure evolution was investigated via in situ WAXS and SAXS. Stretching-induced α′ crystal is more ordered than the cold crystallized one. The PLA was stretched into different ordered structures at different temperatures. The analogous shish-kebab morphology was formed when stretched at higher temperatures. The lamellar crystal with thickness about 10 nm evolutes from stable mesophase.